Matsuo Basho and His Journey in Oku no Hosomichi - Rahman, Aulia (Vocational College of Diponegoro University, 2025)
This study analyzes Matsuo Basho’s Oku no Hosomichi (The Narrow Road to the Deep North) through Carl Thompson’s travel writing theory. The objective is to explore how Matsuo’s poetic travelogue embodies the essential elements of travel writing, such as the narrator's identity, the nature of the journey, cultural encounters, and narrative construction. Using a qualitative descriptive method, this research examines selected passages and haiku from Oku no Hosomichi, focusing on how Matsuo presents his inner reflections, spiritual quest, and observations of the landscape and people he encounters. The analysis reveals that Matsuo’s work documents a physical journey and is a contemplative exploration of self and nature. His style blends lyrical poetry with prose, creating a layered narrative reflecting personal transformation and cultural commentary. Viewed through Thompson’s framework, Oku no Hosomichi exemplifies key aspects of travel writing, including subjective experience, cultural mediation, and temporal distance. The study concludes that Matsuo’s journey transcends mere travel documentation; it becomes a medium for philosophical reflection and aesthetic expression. This research highlights the value of classical Japanese literature as an early and sophisticated form of travel writing, offering insights into how cultural identity, place, and movement are articulated in literary form. The findings also demonstrate the relevance of applying modern theoretical perspectives to traditional texts for a deeper understanding of their literary and cultural significance.